2002
DOI: 10.1046/j.1460-9568.2002.01954.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐cell recording from honeybee olfactory receptor neurons: ionic currents, membrane excitability and odourant response in developing workerbee and drone

Abstract: Whole-cell recording techniques were used to characterize ionic membrane currents and odourant responses in honeybee olfactory receptor neurons (ORNs) in primary cell culture. ORNs of workerbee (female) and drone (male) were isolated at an early stage of development before sensory axons connect to their target in the antennal lobe. The results collectively indicate that honeybee ORNs have electrical properties similar, but not necessarily identical to, those currently envisaged for ORNs of other species. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Larvae have the capability to respond to outside stimuli and inside regulatory cues such as odorant-based communication and immune defense [56, 57]. This is reflected in our data that both bee species observed abundant expression of different odorant binding proteins (OBPs) in the hemolymph (OBP13, log 1.5 Ratio ≥ 3.5 in day 3 pupae in Aml and Acc; OBP14/19d, log 1.5 Ratio ≥ 3.5 in day 5 larvae and day 3 pupae in Aml), and an iron transporting protein (transferrin 1, log 1.5 Ratio ≥ 3.5 in day 5 larvae in Aml).…”
Section: Discussionmentioning
confidence: 99%
“…Larvae have the capability to respond to outside stimuli and inside regulatory cues such as odorant-based communication and immune defense [56, 57]. This is reflected in our data that both bee species observed abundant expression of different odorant binding proteins (OBPs) in the hemolymph (OBP13, log 1.5 Ratio ≥ 3.5 in day 3 pupae in Aml and Acc; OBP14/19d, log 1.5 Ratio ≥ 3.5 in day 5 larvae and day 3 pupae in Aml), and an iron transporting protein (transferrin 1, log 1.5 Ratio ≥ 3.5 in day 5 larvae in Aml).…”
Section: Discussionmentioning
confidence: 99%
“…5-HT was shown to increase the number of sodium spikes elicited by a constant depolarising current although in these cultures only 20% of the cells exhibited action potentials (Mercer et al 1996a). Antennal lobe cells, mushroom body cells and olfactory receptor cells from the honeybee and from M. brassicae also exhibited TTX-sensitive sodium currents that activated between À50 and À30 mV and trains of action potentials could be elicited by depolarising pulses (Kloppenberg et al 1999;Laurent et al 2002;Lucas and Shimahara 2002;Grü newald et al 2004;Wü stenburg et al 2004). Embryonic cockroach neurones in vitro have been reported to exhibit sodium currents and action potentials (Lees et al 1985) but Amar et al (1991) found no fast sodium currents in similar cultures although veratridine induced slow, voltage-dependent, TTX-sensitive currents independent of the fast currents involved in action potential generation.…”
Section: Ionic Currents In Cultured Neuronesmentioning
confidence: 99%
“…The brains of pupae have been used to provide mushroom body cultures from the honeybee, Apis mellifera (Kreisel and Bicker 1992) and D. melanogaster (Kraft et al 1998) and antennal lobe cultures from the honeybee (Kreisel and Bicker 1992), the moth, Mamestra brassicae (Lucas et al 1997), the sphinx moth, Manduca sexta (Mercer et al 1995), the silk moth, Bombyx mori (Park et al 2003) and the cutworm moth, Spodoptera litura (Satoh et al 2005). Identified neuronal cultures have been produced from olfactory receptor cells from Manduca (Stengl and Hildebrand 1990;Hayashi and Hildebrand 1990), M. brassicae (Lucas and Shimahara 2002) and the honeybee (Laurent et al 2002); mechanoreceptor cells from Manduca (Torkkeli and French 1999) and the cockroach (Stockbridge et al 1990); afferent neurones from grasshopper, Schistocerca gregaria, appendages (Cardie et al 1989) and thoracic leg motor neurones from Manduca (Gru¨newald and Levine 1998). Unidentified neuronal cultures continue to be used from the brains of the cockroach, Leucophaea maderae (Petri and Stengl 1999), the cockroach, P. americana (van Eyseren et al 1998), larvae and adults of the tobacco budworm, Heliothis virescens (Lee and Adams 2000) and Drosophila (reviewed by Rohrbough et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of different olfactory receptors in the ORNs allows discrimination between different features of each odor. Besides Drosophila, characterization of ORNs has been reported in other insects, such as mosquitoes, honeybees, and moths (Laurent et al, 2002;Hallem and Carlson, 2004;Ghaninia et al, 2007). Therefore, the ORNs in each functional subtype play an important role in odor encoding for chemical sensing in insects.…”
Section: Introductionmentioning
confidence: 99%